Pengaruh Motivasi Belajar terhadap Kedisiplinan Belajar Siswa Kelas II SDN 1 Towangsan Gantiwarno Tahun Pelajaran 2023/2024 - Retno Isnawati; Bayu Purbha Sakti; Sri Suwartini (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This research is based on the problem of students who are not disciplined in learning in the classroom due to low motivation to learn, students are lazy to do the assignments given by the teacher, students do not pay attention to the teacher during the learning process, and students play during the learning process. The purpose of this study is to describe the influence of motivation on the learning discipline of grade II students at SD 1 Towangsan Gantiwarno, Klaten Regency for the 2023/2024 Academic Year. This type of research is quantitative. Data collection techniques use questionnaires, and documentation. This study took all members of the second grade population of SDN 1 Towangsan which amounted to 13 students. The analysis technique uses a simple linearity test and determination test. The results of the study using descriptive analysis showed that learning motivation was in the high category with a frequency of 9 respondents (69), medium category with a frequency of 3 respondents (23%), while in the low category with a frequency of 1 respondent (8%). Sedangkan kedisiplinan belajar pada kategori tinggi dengan frekuensi sebanyak 4 responden (40)%, kategori sedang dengan frekuensi sedang sebnyak 3 responden (30%), sedangkan dalam kategori rendah dengan frekuensi sebanyak 3 responden (30%).